STUDI POTENSI PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) DI SUNGAI YEH DIKIS BANJAR LEBAH KABUPATEN TABANAN - Ernest Putra, Wahyudi; Sukerayasa, I Wayan; Dwi Giriantari, Ida Ayu (Jurnal SPEKTRUM; Vol 10 No 2 (2023): Jurnal SPEKTRUM, 2023)
Renewable energy must be developed considering the depletion of fossil fuel reserves and the instability of fossil fuel prices. The development and implementation of environmentally friendly renewable energy sources needs serious attention. IESR's calculations in 2019 said that the potential for Micro hydro power plants (PLTMH) in Bali reached 15 MW. This research was conducted due to the presence of sufficient head and water flow as a potential to be PLTMH on the Yeh Dikis river. The purpose of this study is to identify the potential for electrical power that can be generated at the research location on the Yeh Dikis River, Banjar Lebah, Tabanan Regency, and determine the type of turbine to be used. The method used in this research is observation and literature study. The results of measurements and calculations performed, the available discharge potential is 0.381 m3/s and head fall is 8.2 m. The crossflow turbine is a viable option for implementing in the design of this PLTMH system on the Yeh Dikis river. The potential power that can be generated with a turbine efficiency of 0.75 and an assumption of a generator efficiency of 0.9 is 15.516 kW.